Coexistence in long-term managed lakes: Limited evidence of negative impacts of invasive macrophytes on fish communities - Vinícius Londe; Candice M. Prince; S. Luke Flory (Ecological Indicators)
Invasive macrophytes are widespread and can disrupt freshwater ecosystems if not properly managed. Their impact on fish is a topic of ongoing discussion, with studies reporting contrasting results. Utilizing datasets spanning 17 years of monitoring across 34 lakes in Florida, we examined the effects of the primary non-native invaders water hyacinth (Eichhornia crassipes (Mart.) Solms), hydrilla ((Hydrilla verticillata L. f.) Royle), and water lettuce (Pistia stratiotes L.), plus the entire non-native macrophyte assemblage and abiotic variables on fish species richness, Shannon diversity, abundance, length, and biomass. Together, these indicators help assess and manage the impact of invasive species and environmental changes on freshwater ecosystems. Our study was conducted at both habitat and lake scales to ensure a more thorough understanding of potential impacts. We found evidence of a marginally positive influence of hydrilla on fish species richness and abundance, a positive influence of water lettuce on Shannon diversity, and a positive effect of water hyacinth on fish length, all at the habitat scale. Notably, these effects were largely analogous to those of native macrophytes. Water temperature of about 26 °C and dissolved oxygen levels between 5 and 10 mg/L appeared to be optimal for fish. Lakes located in northwest Florida exhibited higher fish diversity and abundance. The integrated use of ecological indicators reveals that long-term management of lakes might limit populations of non-native macrophytes, thereby reducing the adverse effects of invaders on fish communities and facilitating their coexistence. This study highlights the importance of management strategies and long-term monitoring in minimizing the impacts of invasive plants on freshwater ecosystems.